Analisis Tingkat Kebisingan Knalpot Sepeda Motor Produk Industri Kecil - Eko Subandono; Sukoco Sukoco; Mochamad Syamsiro (Universitas Janabadra, 2017)
Automotive industry is one of the promising sector which is growing very fast recently. One of the important automotive component products is exhaust muffler. The present work aims to experimentally study the noise level generated from the racing type of muffler produced from small and medium industry compared with the standard type from the original products. The noise level measurement of motorcycle muffler has been conducted with several parameters including muffler types, glasswool filling, and silencers. The results showed that the increase in engine speed increased the noise generated from motorcycle muffler. Furthermore, the results also showed that the muffler noise level of racing type muffler is much higher than those of the standard muffler noise level. The highest noise level is obtained by HRP muffler, while the lowest is Tegal muffler. Glasswool filling in the muffler reduced the noise level for all four types of racing type mufler. Full glasswool filling can reduce the noise level significantly. The number and dimension of the silencer in the muffler have the prominent effect on the noise level. The increae of hole number in the silencer will be able to reduce the noise level.